Prevalence and risk factors of hypertension and diabetes mellitus in riverine communities in Nigeria’s Niger delta: implications for community-based interventions - Fajola, Akinwumi O.; Isara, Alphonsus O.; Alali, Aloni; Adetula, Bunmi; Akenge, Suodei (International Journal Of Community Medicine And Public Health, 2024)
Background: The global burden of non-communicable diseases is enormous, especially in low- and middle-income countries. This study assessed the prevalence of hypertension and diabetes mellitus and associated factors among adult residents of riverine communities in Niger delta region of Nigeria. Methods: A community-based descriptive cross-sectional study. Adults aged 18 years and above residing in riverine communities who attended a free medical outreach programme were screened for hypertension and diabetes mellitus. Anthropometry and measurements were done using standard methods. Data was analysed using SPSS version 26. Results: Of the 1597 participants, 1066 (66.6%) were females, 470 (29.4%) overweight and 356 (22.3%) were obese. Their mean age was 41.0±14.5 years. The prevalence of hypertension diabetes mellitus and hypercholesterolemia was 37.6%, 3.9% and 65.6% respectively. Significant predictors of hypertension were age ≥40 years (OR =3.86, CI: 2.59-5.75, p<0.001), male sex (OR=1.78, CI: 1.19-2.65, p=0.005), overweight (OR=1.92, CI: 1.19-3.11, p=0.008) and obesity (OR=1.73, CI: 1.05-2.85, p=0.032). No statistically significant association between demographic characteristics and diabetes mellitus was observed. Conclusions: The high prevalence of hypertension and diabetes mellitus in the riverine communities calls for an urgent need to set up community based noncommunicable diseases prevention programmes and then develop and implement effective targeted interventions to help residents of the riverine communities diagnosed with these conditions to better manage the disease.